Optical feedback cavity enhanced absorption spectroscopy with diode lasers. - Baran, S; Hancock, G; Peverall, R; Ritchie, G; van Leeuwen, N (2009)
An optical feedback cavity enhanced absorption spectroscopy (OF-CEAS) apparatus has been developed, using a distributed feedback diode laser centred close to a wavelength of 1596 nm. Light from a V-shaped optical cavity is allowed to feed back to the laser diode, injection seeding the laser at the cavity mode frequencies, and bringing about linewidth narrowing and frequency locking to the cavity resonance. The OF-CEAS technique's expediency and sensitivity have been demonstrated, first on measurements of aerial water absorptions close to 6260.8 cm(-)(1), and then on two carbon dioxide absorptions close to 6261.7 cm(-)(1) which may be used to measure the concentrations of (13)CO(2) and (12)CO(2) isotopologues in a CO(2) sample. Employing a cavity of moderate finesse (F approximately 3500), an acquisition time-reduced minimum detectable absorption coefficient of 5.8 x 10(-)(9) cm(-)(1) s(1/2) has been determined.